The Impact of ChatGPT on English Language Teachers’ Classroom Practices - Rayamajhi, Arjun Jung (Exploration अन्वेषण, 2026)
The rapid development of artificial intelligence (AI) presents many opportunities and challenges for education globally, especially in underdeveloped countries. The aim here is to explore the development of this dynamic use of ChatGPT in secondary school English classes in Nepal. The study is applied by a narrative inquiry approach through exploring the experiences of four English teachers who integrate an AI tool in their language teaching. The information was obtained through extensive interviews with four English teachers, observations of their lessons, and their stories and experiences. Key theme analysis reveals that educators were receptive to increased student input and promoted a personalised learning approach; however, systemic barriers substantially impeded progress. The most pressing factors that have been considered are the deployment of AI, not adequately prepared or aware of pedagogical methods, educational disparities in terms of resources and content quality, but also training, lack of motivation and a poor learning environment where digital literacy deteriorates, and students become overly reliant on it. The research also reveals that, in community schools, irrespective of the availability of resources, some basic capacity-building is necessary before teachers can use latrine platforms safely and effectively. These skills should be fully integrated into the curriculum by the Nepali government, and community schools should give them a chance. It should be monitored, steered and trained to wield tools like ChatGPT appropriately.